Does The Usage Of Drain Reduce Post Thyroidectomy Complications? A Case Control Study - Omar, Asaad S. (Journal of Neonatal Surgery, 2025)
Background: Thyroid surgery is a common operation worldwide. The use of drains in thyroid surgery has been controversial,majority of the surgeons routinely put a drain after thyroid surgery to drain a possible postoperative hemorrhage and prevent formation of seroma. This study was aimed to find comparison in occurrence of complications in relation to use of drain versus no drain after thyroidectomy. Patient and Method:This prospective randomized cross-sectional study included 156 patients who underwent thyroid surgeriesbetween the periods ofJanuary 2017and January 2022with a minimum period of 7 days of follow up. These patients were randomly selected, preoperatively, into two groups whether to put or not to put a drain. Group 1 was 76 patients without drains and group 2 was 80 patients with drains. Results;The mean age of patients was 42.2 years. The majority were females 144 (92.3%). Presentationwas with single nodule or multi-nodular goitre(MNG) was more common than diffuse goitre. Pain was present in only 13.5% of them and pressure symptoms presented in 28.8% of them. The main indication for surgery was suspisious nodule in 44.23% of cases ,followed by MNG with pressure symptoms in about 28.85%, then MNG with pain in 12%, diffuse toxic goitre in 13.46% and lastly cystic lesion in 1.28%. The incidence of seroma and subcutaneous hematoma was examined in relation to certain patient and surgical operation-related factors, such as age, which showed a statistically significant relationship with a p-value of 0.019, but the incidence of seroma did not show a significant relationship with the length of the surgical procedure or hospital stay, and whether or not a drain was placed did not significantly affect the incidence of seroma orsubcutaneous hematoma post-operativelythis difference was statistically not significant with a p-value of 0.82. Conclusion:Minor complications are more common following thyroid surgery, routine drain placement after thyroidectomy does not reduce complications such as seroma or hematoma, as there is no significant difference between those patients with and without drainage.Moreover, avoiding drain improve the possibility of post operative outcomes like decreasing morbidity and recurrent hospital admissions by reducing such complications